Targeted Gene Delivery to Muscle Cells In Vitro and In Vivo Using Electrostatically Stabilized DNA-Peptide Complexes - Anna Egorova; Sergei Chepanov; Sergei Selkov; Igor Kogan; Anton Kiselev (MDPI AG, 2024)
Genetic constructs must be delivered selectively to target tissues and intracellular compartments at the necessary concentrations in order to achieve the maximum therapeutic effect in gene therapy. Development of targeted carriers for non-viral delivery of nucleic acids into cells, including those in muscle, which is one of the most challenging tissues to transfect in vivo, remains a topical issue. We have studied ternary complexes of plasmid DNA and an arginine-histidine-rich peptide-based carrier coated with a glutamate-histidine-rich polymer bearing skeletal muscle targeting peptide (SMTP) for the gene delivery to muscle tissue. The relaxation of the ternary complexes after polyanion treatment was assessed using the ethidium bromide displacement assay. The developed polyplexes were used to transfect C2C12 myoblasts in full-media conditions, followed by analysis of their toxic properties using the Alamar Blue assay and expression analysis of lacZ and GFP reporter genes. After delivering plasmids containing the GFP and lacZ genes into the femoral muscles of mdx mice, which are model of Duchenne muscular dystrophy, GFP fluorescence and β-galactosidase activity were detected. We observed that the modification of ternary polyplexes with 10 mol% of SMTP ligand resulted in a 2.3-fold increase in lacZ gene expression when compared to unmodified control polyplexes in vivo. Thus, we have demonstrated that the developed DNA/carrier complexes and SMTP-modified coating are nontoxic, are stable against polyanion-induced relaxation, and can provide targeted gene delivery to muscle cells and tissues. The results of this study are useful for a range of therapeutic applications, from immunization to amelioration of inherited neuromuscular diseases.